An investigation on cognition of breast cancer among female college students (女大学生乳腺癌认知情况调查研究) - WANG Xiaoqian (王潇倩); SUI Tingting (隋婷婷); WEI Ying (魏莹); SANG Meijie (桑梅洁); WANG Yanzhi (王艳芝) (Journal of International Translational Medicine Limited, 2021)
Objective To understand the female college students' cognition of breast cancer knowledge, and provide scientific basis for health education in colleges and universities in the future. Methods Based on the existing questionnaire, female college students were taken as the research objects, The questionnaire was distributed randomly and the survey was conducted online. Results Totally 550 questionnaires were distributed and 500 were valid, with effective recovery rate of 90. 91%. There was a relatively low awareness rate of breast cancer knowledge among female college students. Female college students majored in Medical science were more knowledgeable in prevention of breast cancer compared with those who were not majored in Medical science. Conclusion Female college students have a low cognition level of breast cancer, it is necessary for colleges and universities to carry out relevant publicity and education, especially for non-medical professional students and low-grade professional students, to improve the self-health awareness of female college students, actively take correct preventive measures to reduce the incidence of breast cancer (目的 了解在校女大学生对乳腺癌相关知识的认知情况, 以为高校今后开展乳腺癌疾病健康教育提供科学依据。方法 自行设计调查问卷, 通过"问卷网"在线问卷调查平台对多所大学的在校女大学生进行线上问卷调查。结果 共发放问卷550份, 回收有效问卷500份, 有效回收率90. 91%。在校女大学生的乳腺癌相关知识掌握率偏低, 医学专业的女大学生乳腺癌预防相关知识的整体掌握情况优于非医学专业的女大学生。结论 在校女大学生的乳腺癌相关知识掌握情况不容乐观。高校应加强相关宣传教育, 尤其针对非医学专业的女大学生要开展更深入的宣教, 从而提高在校女大学生的自我保健意识, 采取正确的预防措施, 降低乳腺癌的发病率。)